2018
DOI: 10.1007/s12671-018-0951-y
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Formal and Informal Mindfulness Practice and Associations with Wellbeing

Abstract: Mindfulness has transdiagnostic applicability, but little is known about how people first begin to practice mindfulness and what sustains practice in the long term. The aim of the present research was to explore the experiences of a large sample of people practicing mindfulness, including difficulties with practice and associations between formal and informal mindfulness practice and wellbeing. In this cross-sectional study, 218 participants who were practicing mindfulness or had practiced in the past complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 30 publications
8
105
0
4
Order By: Relevance
“…We also looked for a possible distinct effect of the approximate total amount of formal and informal practices and found that both practices were related to equanimity scores. Supporting this finding, both informal and formal practices have been related to well-being in other studies and seem more predictive of psychological flexibility than formal practice frequency (Birtwell et al, 2018). We also explored possible relations between the frequencies of different types of meditations and equanimity scores.…”
Section: Discussionsupporting
confidence: 58%
“…We also looked for a possible distinct effect of the approximate total amount of formal and informal practices and found that both practices were related to equanimity scores. Supporting this finding, both informal and formal practices have been related to well-being in other studies and seem more predictive of psychological flexibility than formal practice frequency (Birtwell et al, 2018). We also explored possible relations between the frequencies of different types of meditations and equanimity scores.…”
Section: Discussionsupporting
confidence: 58%
“…Formal practice is an investment of time that is explicitly done in the practice of mindfulness or meditation. Whereas, informal practice is a process of 'weaving' the practice of mindfulness in existing routines through involvement in moments of mindfulness such as mindful eating (Birtwell, Williams, van Marwijk, Armitage, & Sheffield, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness practice is needed to create an effect which is beneficial related to the role of the practice itself formally and informally. Understanding this issue is essential to support the maintenance of these mindfulness practices and to maintain the endurance and prosperity in the long term (Birtwell, Williams, van Marwijk, Armitage, & Sheffield, 2018). Mindfulness practice is an effective strategy to improve leadership (Wasylkiw et al, 2015).…”
Section: Mindfulnessmentioning
confidence: 99%